2018
DOI: 10.1007/s11934-018-0845-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Overactive Bladder in Older Women

Abstract: Frailty, functional and cognitive impairment, multimorbidity, polypharmacy, estrogen deficiency, and remaining life expectancy are important clinical factors to consider and may impact OAB symptom management in older women. Third-line therapies, particularly PTNS, may be preferable over second-line therapy in some cases. Due to the complexity within this population, the standard treatment algorithms may not be applicable, thus a broader, more holistic focus is recommended when managing OAB in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
(68 reference statements)
0
28
0
2
Order By: Relevance
“…In frailty, many changes in the urinary system due to aging may be more serious. For example, a study evaluating frailty with low gate speed found that overactive bladder was higher in frail patients, regardless of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…In frailty, many changes in the urinary system due to aging may be more serious. For example, a study evaluating frailty with low gate speed found that overactive bladder was higher in frail patients, regardless of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with aging, neurological, anatomical, and biochemical changes occur in the bladder function and these changes may predispose the patients to the development of OAB symptoms. 40 The increased prevalence in elderly people has been largely associated with age-related changes in the lower urinary tract (inhibited detrusor contractions, reduced bladder filling sensation and bladder capacity, and higher postvoiding residual volumes). 41 Since our patient group consists of young patients, age-related changes are not expected.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant overlap in the diagnosis of OAB and the genitourinary syndrome of menopause, and the use of vaginal oestrogen in this setting is efficacious in the treatment of urinary incontinence by improving urinary urgency, frequency and bladder capacity. 12 Care should be taken when prescribing topical oestrogen for patients with a history of breast or endometrial malignancy.…”
Section: Treatment Of Oabmentioning
confidence: 99%